2008
DOI: 10.1097/01720610-200811000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Scoliosis: A straightforward approach to diagnosis and management

Abstract: Scoliosis should be no more intimidating to manage than acute otitis media. This article reviews how to treat patients with the condition before and after referral to a specialist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 21 publications
0
13
0
4
Order By: Relevance
“…Approximately 85% of cases are idiopathic. (1,2) Based on the age of presentation, scoliosis is further categorised as infantile, juvenile or adolescent idiopathic. Adolescent idiopathic scoliosis (AIS), which accounts for the majority of the three categories, presents at age ten and lasts till the end of growth.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 85% of cases are idiopathic. (1,2) Based on the age of presentation, scoliosis is further categorised as infantile, juvenile or adolescent idiopathic. Adolescent idiopathic scoliosis (AIS), which accounts for the majority of the three categories, presents at age ten and lasts till the end of growth.…”
Section: Introductionmentioning
confidence: 99%
“…27 Screening by the Adams forward test alone have shown to be inadequate due to the low specificity in certain curves and led to increased referrals, hence the addition of scoliometer measurement is considered more practical. 4,6,9,27 Moreover, Grivas TB et al, reported a more efficient screening by the use of a sitting forwardbending position, providing a better assessment of trunk asymmetry with a more stable posture demonstrating a better surface spinal deformity. 28 To reduce the cost effectiveness and inappropriate radiation exposure, suggestions have been laid out to minimize the risks.…”
Section: Discussionmentioning
confidence: 99%
“…16 The time of maximum progression coincides with Tanner stages 2 and 3, that is after the onset of pubertal growth spurt. 6 The Risser grade is considered to be a better predictor of growth potential. Complete ossification (100%)…”
Section: Symptomatic Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…(10) A retinocoroidite é a manifestação mais importante da doença e a lesão pode se apresentar ao exame fundoscópico de uma forma ativa ou cicatrizada, e está associada à considerável perda de campo visual quando ocorre próximo ao nervo óptico. (11,12) A doença é principalmente adquirida através da ingestão de cistos presentes em carnes cruas ou mal cozidas, especialmente suínas, e através de frutas e verduras mal lavadas contendo os cistos (9,10) . Outra via de transmissão é a transplacentária, na qual se a gestante adquirir a primo infecção durante a gestação, o feto será infectado, sendo que 85% destes desenvolvem retinocoroidite durante a infância ou adolescência.…”
unclassified